(untitled) (TAMADDUN NURI JURNALI, 2024)
This article covers the scientific interpretation of the phenomenon of gradation in Uzbek educational vocabulary, the state of implementation of the law of gradation in educational vocabulary, and interpretations such as lexicographic interpretation in educational dictionaries.